2007
DOI: 10.1021/jf070564n
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Hydrogel Particles by Thermal Treatment of β-Lactoglobulin−Chitosan Complexes

Abstract: Molecular complexes based on proteins and ionic polysaccharides have considerable potential for encapsulation of functional food components, but their widespread utilization is limited because their structure is highly sensitive to pH and ionic strength. We have investigated the possibility of creating stable hydrogel particles by thermal treatment of protein (beta-lactoglobulin) and cationic polysaccharide (chitosan) mixtures. Mixed solutions of beta-lactoglobulin (0.5 wt %) and chitosan (0.1 wt %) were prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 40 publications
2
38
0
2
Order By: Relevance
“…1. Hong and McClements (2007b) reported similar results, and concluded that the b-Lg and chitosan formed soluble complexes at pH 4.5 prior to heating, owing to electrostatic attraction between cationic groups on the chitosan, and anionic patches on the b-Lg surface.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…1. Hong and McClements (2007b) reported similar results, and concluded that the b-Lg and chitosan formed soluble complexes at pH 4.5 prior to heating, owing to electrostatic attraction between cationic groups on the chitosan, and anionic patches on the b-Lg surface.…”
Section: Resultsmentioning
confidence: 64%
“…The coacervate exists in equilibrium with a dilute supernatant (Microtek Lab Inc., 2008). Recently, many research articles have been published regarding coacervation between whey proteins and polysaccharides (Cooper, Dubin, Kayitmazer, & Turken, 2005;de Kruif, Weinbreck, & de Vries, 2004;Hong & McClements, 2007a, 2007bSanchez, Mekhloufi, & Renard, 2006;Schmitt, Sanchez, Thomas, & Hardy, 1999;Wang, Lee, Wang, & Huang, 2007). Schmitt et al (1999) previously evaluated the compatibility of b-Lg and acacia gum in aqueous medium as a function of pH values between 3.5 and 5.0, and concluded that as the biopolymer content was increased at pH values of 3.6 and 4.2, the relative solubility of b-Lg increased, probably as the result of the self-suppression of complex coacervation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has already been a considerable amount of research on the development of this type of biopolymer-based particle. Biopolymer particles have been formed by electrostatic complexation and thermal treatment of -lactoglobulin and chitosan in aqueous solutions (Hong & McClements, 2007), as well as -lactoglobulin and pectin (Jones, Decker, & McClements, 2009;Jones & McClements, 2008). Biopolymer particles formed by electrostatic complexation of proteins and polysaccharides have also been used to encapsulate hydrophobic nutraceuticals.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Recently, it has been shown that biopolymer particles can be formed by heating globular protein-cationic polysaccharide electrostatic complexes above the thermal denaturation temperature of the protein. 14,15 These particles were shown to remain intact when the pH was subsequently adjusted to values where the complexes would be expected to dissociate at ambient temperature. In the present study, we examine the stability of biopolymer particles formed by heating a globular protein (β-lactoglobulin) and an anionic polysaccharide (sugar beet pectin) under conditions where they form an electrostatic complex (pH 5).…”
Section: Introductionmentioning
confidence: 99%